PEMBUATAN SERTIFIKAT HAK MILIK TANAH YANG BERBATASAN DENGAN KAWASAN HUTAN: Creating Land Ownership Certificates Bordering Forest Areas - Ardika, Tusan; Titawati, Titin (Ganec Swara, 2025)
This research examines the process of obtaining land ownership certificates bordering forest areas. The background to this research is the lack of legal skills among village residents regarding the administrative requirements required to fulfill the document requirements for land ownership certificates. This research is a type of normative-empirical research using a legislative approach and conceptual analysis. The legal sources used are primary, secondary, and tertiary legal materials. The research findings indicate that many residents are unaware of the administrative requirements required to obtain land title certificates for land bordering forests. By forming groups, residents can report to the village office sporadically and obtain a recommendation letter from the Forestry Service. This allows them to proceed to the Village Head/BPN (National Land Agency) to obtain a land title certificate. Based on the research findings and the conclusions in the discussion chapter, the author proposes the following recommendations: The quality of land certificates will improve if the community actively participates in the land certificate registration process. The government needs comprehensive information about the creation and benefits of certificates, especially for land bordering protected forests, throughout Indonesia, to broaden public awareness.